Living standards and mortality since the Middle Ages - Morgan Kelly; Cormac Ó Gráda (University College Dublin, UCD School of Economics, 2010)
Existing studies find little connection between living standards and mortality in England, but go back only to the sixteenth century. Using new data on inheritances, we extend estimates of mortality back to the mid-thirteenth century and find, by contrast, that deaths from unfree tenants to the nobility were strongly affected by harvests. Looking at a large sample of parishes after 1540, we find that the positive check had weakened considerably by 1650 even though real wages were falling, but persisted in London for another century despite its higher wages. In both cases the disappearance of the positive check coincided with the introduction of systematic poor relief, suggesting that government action played a role in breaking the link between harvest failure and mass mortality.
hdl:10197/2659
Keywords: N33; 330